2011
DOI: 10.1089/cyber.2010.0307
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cybercrime Perpetrators and the Strategies They Employ in Nigeria

Abstract: A lot has been written on cybercrime and its prevention, but the problem has proved particularly resilient to remedial action. Desperate and vulnerable individuals in every continent continue to fall into its trap. Despite this, there is dearth of descriptive study that attempts to unravel the strategies employed by the perpetrators in Nigeria, as an important precondition for workable and reliable policy direction to address the problem. This article has filled this gap by using data from 40 cybercrime perpet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The term Yahoo-Boys not only signifies that the perpetrators of the infamous yahoo-yahoo are predominantly male (Cross 2018;Lazarus 2018), but also indicates that they are young. Other empirical studies support the youthhood 4 of Yahoo-Boys as well (e.g., Aransiola and Asindemade 2011;Lazarus and Okolorie 2019).…”
Section: Money Doublers and Money Doublingmentioning
confidence: 81%
“…The term Yahoo-Boys not only signifies that the perpetrators of the infamous yahoo-yahoo are predominantly male (Cross 2018;Lazarus 2018), but also indicates that they are young. Other empirical studies support the youthhood 4 of Yahoo-Boys as well (e.g., Aransiola and Asindemade 2011;Lazarus and Okolorie 2019).…”
Section: Money Doublers and Money Doublingmentioning
confidence: 81%
“…(p. 397) Therefore, a common suggestion to combatting cybercrime in western Africa is the creation of more jobs for youth (Boateng et al, 2011;Uddin & Uddin, 2013). The typical Nigerian or Ghanaian Internet scammer, for example, is male, under the age of 30, from a lower-income background, and resides near urban centers with easy access to Internet cafes (Aransiola & Asindemade, 2011;Warner, 2011), indicating that the lack of opportunity, combined with easy-to-access computer hard drives and Internet capabilities, makes the temptation too great for cybercriminals. Further development of social programs in the region may help to remove would-be cybercriminals from the trade.…”
Section: Resultsmentioning
confidence: 99%
“…These cybercriminals will typically contact Westerners over social media sites (i.e., Facebook or Twitter) or sometimes even via online dating Web sites (such as eHarmony.com or Match.com) and establish a rapport with an individual using this false identity (Warner, 2011). The fraudster will then cultivate a relationship with their victim, which oftentimes is romantic in nature (Aransiola & Asindemade, 2011;Warner, 2011). Over time, they will ask their victim for personal information, such as bank and financial information, names of close relatives, and passwords, often promising some benefit in exchange (Warner, 2011).…”
Section: Common Cybercrime Schemesmentioning
confidence: 99%
“…They found that offenders draw on gendered themes to align their actions with cultural expectations of masculinity and femininity. For example, qualitative studies found that while Nigerian men (and boys) predominate in “cybercrime” as perpetrators, most Nigerians involved in “cybercrime” types, in general, are involved in cyber‐fraud in particular (e.g., Aransiola and Asindemade ; Lazarus ; Lazarus and Okolorie ). Women, however, play subordinate roles, such as the retrieval of fraud proceeds (e.g., Jegede et al .…”
Section: Overview Of Gender Gap Onlinementioning
confidence: 99%